Monitoring rubber plantation distribution on Hainan Island using Landsat OLI imagery. Issue 8 (18th April 2018) - Han, Pengpeng; Chen, Jinsong; Han, Yu; Yi, Lin; Zhang, Yannan; Jiang, Xiaoli
ABSTRACT: Rubber expansion has been widely explored at various scales due to its increasing environmental and socio-economic impact and the global demand for natural rubber products. However, accurate and up-to-date maps and large-scale monitoring of rubber plantation spatial distribution are not yet available. In this article, we developed a simple algorithm for rapidly and accurately mapping rubber plantations on Hainan Island, China, by combining survey samples and Landsat 8 Operational Land Imager data from 2014 in order to understand their spatial distribution. The results showed that rubber plantations are distinguishable from other land-cover types by band value changes, vegetation index changes, and phenological phase changes (defoliation and foliation) and can be accurately extracted from multi-temporal Landsat images using a decision tree method and Google Earth Engine. This method results in a high overall classification accuracy of 92.17% with a corresponding κ of 84.33%. Rubber plantations are concentrated in the northwest of Hainan Island and gradually decrease to the south and east. Most plantations are found in the 50–500-m elevation range, with few found outside this range. We believe that the proposed approach will have significant implications for mapping and monitoring rubber spatial distribution at regional scales.